1987
DOI: 10.1103/physrevlett.58.120
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of magnetic fluctuations and edge transport in the Doublet III tokamak

Abstract: A clear correlation between incoherent magnetic fluctuations and transport in the outer region of the plasma was observed in a set of Doublet III beam-heated discharges which experienced repetitive transitions between a poor-confinement phase and an improved-confinement phase. The fluctuations and associated transport are consistent with a model based on an assembly of saturated microtearing modes.PACS numbers: 52.55. Fa, 52.25.Fi, Observations of improved energy confinement ("//mode" discharges) in tokamaks 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 13 publications
2
34
0
Order By: Relevance
“…1, at the L to H transition, the magnetic fluctuations in the 10 to 30 kHz range decrease abruptly. This change in the frequency spectrum is seen most clearly on the rnagnetic probes located where the inner and outer separatrix field lines intersect the wall of the vacuum vessel, possibly due to line-tying effects (Ohyabu et al, 1988). It is also seen on magnetic probes located on the centerpost of the vacuum vessel near the vessel midplane.…”
Section: Transition Phenomenamentioning
confidence: 85%
“…1, at the L to H transition, the magnetic fluctuations in the 10 to 30 kHz range decrease abruptly. This change in the frequency spectrum is seen most clearly on the rnagnetic probes located where the inner and outer separatrix field lines intersect the wall of the vacuum vessel, possibly due to line-tying effects (Ohyabu et al, 1988). It is also seen on magnetic probes located on the centerpost of the vacuum vessel near the vessel midplane.…”
Section: Transition Phenomenamentioning
confidence: 85%
“…It has been shown that for some tokamak discharges, MTMs are unstable primarily in the plasma edge region, 11,12 regulating heat transport, and, possibly, pedestal evolution between edge-localized modes. 9 Moreover, it has been found that in plasmas where b e (ratio of the electron pressure to the magnetic pressure) and collisionality are sufficiently high, MTMs can become the dominant instability contributing to electron transport in the plasma core.…”
Section: Introductionmentioning
confidence: 99%
“…One well-known instability is the microtearing mode driven by electron temperature gradient [4]. A nonlinear theory for the saturation level of the instability was developed [5], but it was found later that these modes should be stable in conventional tokamaks [6] except near the plasma edge where electron temperature is low [7,8]. Plasma parameters in current spherical tokamak (ST) experiments are quite different from conventional tokamaks, and microtearing modes can be the most unstable mode in National Spherical Torus Experiment (NSTX) [9] and MegaAmpere Spherical Tokamak (MAST) [10] over a certain range of parameters.…”
mentioning
confidence: 99%